We the Leaders: In Order to Form a Leaderful Organization - Joseph A. Raelin (Journal of Leadership & Organizational Studies, 2005)
This article endeavors to develop an emerging paradigm of leadership for our organizations known as "leaderful practice." Leaderful practice constitutes a direct challenge to the conventional view of leadership as "being out in front. " It is submitted that in the 21st Century organization, everyone will need to share the experience of serving as a leader, not sequentially, but concurrently and collectively. In other words, leaders need to co-exist at the same time and all together. In addition, each member of an organization will be encouraged to make a unique contribution to its growth, both independently and interdependently with others. In this sense, organizational members will aspire to become fervently collaborative, which in turn is derived from their compassion toward other human beings. Their well-developed sense of self permits them to develop a deep consideration of others. Thus, the article makes the case that the only possible way to lead ourselves out of trouble in management is to become mutual and to share leadership.
Keywords: M10; M12; M53; O15; J28; 650; Leadership; Leadership development; Collaboration; Shared leadership; Self-managing teams; Employee development; Empowerment; Stewardship